HUBUNGAN VARIABEL ORGANISASI DAN PSIKOLOGIS DENGAN KINERJA PEGAWAI PUSKESMAS BENDAN KOTA PEKALONGAN DALAM ERA JAMINAN KESEHATAN NASIONAL - Nurul Rizki Fitria; Septo Pawelas Arso; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
National Health Insurance requires efforts to improve access and quality of health services in first-level health facilities. In order for services to be implemented properly one of the important factors is certainly the performance of health workers who are the spearhead of the service. The performance of Bendan’s puskesmas  employees is known to be decreasing so it can affect the quality of service. According to Gibson, performance is influenced by organizational and psychological variables. The purpose of this research is to analyze the correlation between organizational variable consisting of infrastructure, service incentive, job design, leadership, and psychological variable that is perception, attitude, and motivation with staff’s performance. This research uses quantitative method with cross sectional approach, and was conducted at Bendan’s Puskesmas Pekalongan. Respondents are 47 people Bendan’s puskesmas staff. Data analysis including univariate analysis with the presentation of frequency distribution tables and bivariate analysis using the chi square test. The results of univariate analysis showed that the performance of  puskesmas employees was not good and incentive services were not appropriate, but infrastructure, work design, leadership, perceptions, attitudes and motivations tended to be good. The result of bivariate analysis shows that all variables have correlation with the performance of Bendan puskesmas personnel in National Health Insurance era such as infrastructure facilities (pvalue = 0.028), service incentive (pvalue = 0.014), job design (pvalue = 0.024), leadership (pvalue = 0.028), perception (pvalue = 0.012), attitude (pvalue = 0.047), and motivation (pvalue = 0.004). It is recommended to BLUD Puskesmas Pekalongan city to properly organize the prevailing remuneration policy in the form of incentives according to the workload to improve the performance of puskesmas employees.